The Effect of Open Learning Achievement in Studying Physics Inquiry from the Scientific Working of Students in SMAN 1 Blitar - Ratnaningtyas Martuti (Jurnal Pendidikan Sains, 2013)
Pengaruh Pembelajaran Open Inquiry terhadap Prestasi Belajar Fisika Ditinjau dari Kerja Ilmiah Siswa SMA Negeri 1 Blitar Abstract:  Learning physics are still teacher-centered learning. Students tend to be passive in following the teaching of physics. While there are experiments to be followed, the students carry out the instructions were very clear with no cognitive challenges and physics learning achievement is less. Open inquiry learning provides learning opportunities for students to develop the ability of scientific work. The design of the study is a 2x2 factorial with purposive sampling technique. The population is all class XI IPA SMAN 1 Blitar in odd semester of academic year 2012/2013 with 6 classes as samples. The experimental group and the control group was divided into two groups containing 36 students. Data collection instrument is a scientific work and student achievement. Data were analyzed by two-way ANOVA and Tukey test. The results showed: (1) learning achievement of students studying physics using open inquiry learning is higher than with conventional learning, (2) there is an interaction between the learning ability of open inquiry and scientific work on physics learning achievement, (3) study the physics student achievement has the ability of high scientific work and learn to use open inquiry learning is higher than learning with conventional learning, and (4) achievement of students who have studied physics low scientific work ability by learning using open inquiry learning is lower than learning with conventional learning. Key Words: open inquiry, academic achievement, scientific work. Abstrak: Pembelajaran fisika yang digunakan selama ini masih banyak berpusat kepada guru. Siswa cenderung pasif dalam mengikuti pembelajaran fisika. Walaupun ada eksperimen yang harus diikuti, siswa melaksanakan petunjuk yang sangat jelas tanpa ada tantangan kognitif dan prestasi belajar fisika kurang. Pembelajaran open inquiry menyediakan kesempatan belajar siswa untuk mengembangkan kemampuan kerja ilmiah. Rancangan penelitian yang digunakan adalah faktorial 2x2 dengan teknik purposive sampling. Populasinya adalah seluruh kelas XI IPA SMA Negeri 1 Blitar semester gasal tahun pelajaran 2012/2013 dengan 6 kelas sebagai sampel. Kelompok eksperimen dan kelompok kontrol terbagi menjadi dua kelompok yang berisi 36 siswa. Instrumen pengambilan data adalah kerja ilmiah dan prestasi belajar siswa. Data dianalisis dengan Anava dua jalan serta uji Tukey. Hasil penelitian menunjukkan: (1) prestasi belajar fisika siswa yang belajar menggunakan pembelajaran open inquiry lebih tinggi daripada dengan pembelajaran konvensional, (2) terdapat interaksi antara pembelajaran open inquiry dan kemampuan kerja ilmiah terhadap prestasi belajar fisika, (3) prestasi belajar fisika siswa yang mempunyai kemampuan kerja ilmiah tinggi dan belajar menggunakan pembelajaran open inquiry lebih tinggi daripada belajar dengan pembelajaran konvensional, dan (4) prestasi belajar fisika siswa yang mempunyai kemampuan kerja ilmiah rendah dengan belajar menggunakan pembelajaran open inquiry lebih rendah daripada belajar dengan pembelajaran konvensional.Kata kunci: open inquiry, prestasi belajar, kerja ilmiah